PENGELOLAAN KEUANGAN PADA MASYARAKAT PENERIMA BANTUAN KELUARGA HARAPAN (PKH) DI DESA KEDIRI SELATAN KABUPATEN LOMBOK BARAT - Sukriati (Yayasan Nusantara Hasana Berdikari, 2023)
This research aims to determine the financial management of people who receive Family Hope Assistance (PKH) in South Kediri Village, West Lombok Regency, NTB. Financial management in this research is seen from a person's knowledge of priorities for items to spend and savings. Aid recipients are poor people with uncertain incomes, so they must be able to manage their finances well to achieve prosperity and not only rely on assistance from the government. This research uses a qualitative method - phenomenology, this research data consists of data from the community receiving aid, interview results, notes from interviews when the research was carried out. Data analysis in this research (qualitative) starts from data reduction, data presentation and drawing conclusions. Based on the results of the research conducted, it was found that financial management in the South Kediri village community, West Lombok Regency was owned by five respondents, three of whom were able to manage their finances well.